If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-3x + 6) = -13x + 8 Reorder the terms: 4(6 + -3x) = -13x + 8 (6 * 4 + -3x * 4) = -13x + 8 (24 + -12x) = -13x + 8 Reorder the terms: 24 + -12x = 8 + -13x Solving 24 + -12x = 8 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 24 + -12x + 13x = 8 + -13x + 13x Combine like terms: -12x + 13x = 1x 24 + 1x = 8 + -13x + 13x Combine like terms: -13x + 13x = 0 24 + 1x = 8 + 0 24 + 1x = 8 Add '-24' to each side of the equation. 24 + -24 + 1x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + 1x = 8 + -24 1x = 8 + -24 Combine like terms: 8 + -24 = -16 1x = -16 Divide each side by '1'. x = -16 Simplifying x = -16
| 15+3r-4=1+7r | | 10+2t=18 | | (4n+11)+2(4n+11)=195 | | -15v-40=2-8v | | d/1.2=6 | | 6x-24=-12 | | -18x^4-57x^3+10x^2=0 | | 30=t/7 | | -6x-8+4x=-7x-2 | | -5-8-56n=-8 | | 18=4v+2 | | 5.2a+13=70.2 | | -3x+6=-4x-6 | | 11+3x=170 | | 8z^2-36z+36=20 | | 9x^2=10x | | -7f+10w= | | 4y-13=59 | | 3-a=18 | | 16=2z+4 | | 2y=2y(y-1) | | -5(x-4)=-6(x+8) | | 2y+-3=50 | | 16+2n=-58 | | 9x-32=-5x+52 | | 400-15x=-5000 | | 5r=170 | | 3+3h=18 | | 18-13+n=9 | | (2k^2)-12=12k | | 4+2g=14 | | .01(x+7)=3.5 |